(untitled) (Research, Society and Development, 2022)
A large amount of biomass is available in Brazil, which may give an alternative for pellet production. With the market constantly growing, the search for raw materials with the potential for energy generation has become a necessity in serving sector demands. Eucalyptus sp. and Pinus sp. are the main sources of timber in Brazil. Therefore, the main objective of this study was to evaluate the quality of pellets produced with different blend proportions of Eucalyptus sp. and Pinus sp. wood particles from reforestation. The percentages of eucalyptus in relation to pine were 0, 10, 20, 50, 80 and 90%. Biomass characterization was performed. The pellets were produced in a lab-scale horizontal pelletizing matrix with a heated steam system. The pellets were evaluated for their physical, chemical, energetic and mechanical properties. The higher heating value decreased with an increasing percentage of Eucalyptus sp. in the blend. The chlorine and ash contents were within the range established by the international parameters for wood pellets. The mean mechanical durability of the produced pellets was 93%. Pellets with 80% eucalyptus and 20% pine stood out for their density, compaction rate and mechanical properties.